New Ideologies on Scarlett Whitening Advertisement: Interpreting Symbols of New Masculinity - Ariella, Jihan; Putrib, Citra Fransisca Indah Lestari Dano; Usu, Novi R; Talani, Noval Sufriyanto (Universitas Brawijaya, 2023)
Masculinity came from the construction of maleness, which means it is made and not born, neither inherent nor natural. The evidence of different masculinity shows in Scarlett Whitening's advertisement. Song Joong Ki, a man and South Korean actor who became the brand ambassador of a skincare brand in Indonesia, shows masculinity in South Korea. The symbols displayed in Scarlett Whitening's advertisement